The role of ischemic preconditioning and pentoxifylline in intestinal ischemia/reperfusion injury of rats - Oliveira,Teresinha Regina Ribeiro de (2017)
Abstract Purpose: To investigate the role of ischemic preconditioning (IPC) and pentoxifylline (PTX) in intestinal mucosa ischemia/reperfusion injury (IR). Methods: Thirty rats were assigned to 5 groups (N=6): (CG): no clamping of the superior mesenteric artery (90 min.); (IR-SS): saline + ischemia (30 min.) + reperfusion (60 min.); (IR-PTX): PTX + ischemia (30min.) + reperfusion (60 min.); (IPC-IR-SS): 5 min. of ischemia + 5 minutes of reperfusion (IPC) + saline + ischemia (30 min.) + reperfusion (60 min.); (IPC-IR-PTX ): 5 min. of ischemia + 5 min. of reperfusion (IPC) + PTX + 30 min. of I + 60 minutes of R. Results: The IR-PTX, IPC-IR-SS and IPC-IR-PTX groups had significantly lower scores of mucosa damage than the IR-SS group. IR-PTX group showed higher scores than the IPC-IR-PTX group, in accordance with the hypothesis of a favorable effect of IPC alone or in association with PTX. Additionally, IPC-IR-SS had a higher damage score than the IPC-IR-PTX. The villi height and crypt depth were similar in all groups. The villi height in the IR-SS was significantly lower. Conclusion: Ischemic preconditioning or pentoxifylline alone protect the intestinal mucosa from ischemia/reperfusion injury. However, they do not have a synergistic effect when applied together.